SAMHD1 Gene Mutations Are Associated with Cerebral Large-Artery Atherosclerosis. (4th October 2015) - Li, Wei; Xin, Baozhong; Yan, Junpeng; Wu, Ying; Hu, Bo; Liu, Liping; Wang, Yilong; Ahn, Jinwoo; Skowronski, Jacek; Zhang, Zaiqiang; Wang, Yongjun; Wang, Heng
Abstract : Background . To investigate whether one or more SAMHD1 gene mutations are associated with cerebrovascular disease in the general population using a Chinese stroke cohort. Methods . Patients with a Chinese Han background (N = 300 ) diagnosed with either cerebral large-artery atherosclerosis (LAA, n = 100 ), cerebral small vessel disease (SVD, n = 100 ), or other stroke-free neurological disorders (control, n = 100 ) were recruited. Genomic DNA from the whole blood of each patient was isolated, and direct sequencing of the SAMHD1 gene was performed. Both wild type and mutant SAMHD1 proteins identified from the patients were expressed in E. coli and purified; then their dNTPase activities and ability to form stable tetramers were analysed in vitro . Results . Three heterozygous mutations, including two missense mutations c.64C>T (P22S) and c.841G>A (p.E281K) and one splice site mutation c.696+2T>A, were identified in the LAA group with a prevalence of 3%. No mutations were found in the patients with SVD or the controls (p = 0.05 ). The mutant SAMHD1 proteins were functionally impaired in terms of their catalytic activity as a dNTPase and ability to assemble stable tetramers. Conclusions . Heterozygous SAMHD1 gene mutations might cause genetic predispositions that interact with other risk factors, resulting in increased vulnerability to stroke.